Administration of midazolam as sedative premedication for paediatric patients - Kalibatienė, Lina; Macas, Andrius; Lukošienė, Laura; Ragaišis, Vytautas; Kubilius, Ričardas (Acta medica Lituanica, 2012)
The paper aims to discuss effective presurgical modalities for reducing preanesthetic and preoperative anxiety in children. It reviews the existing research on psychological interventions and sedative premedication for presurgical anxiety management. Psychological and behavioural pre operative preparation of children, through presurgical preparation programs, combined with parental presence during induction of anaesthesia are regarded as alternatives to sedative premedication. A combination of these preparation strategies with midazolam premedication is presented as an effective way of helping children cope with preanesthetic and pre operative anxiety. It is highlighted that the use of low dose midazolam is sufficiently safe and beneficial if alternatives to sedative premedication prove ineffective, especially when dealing with increased feelings of anxiety immediately before anesthesia and the surgery.